2020
DOI: 10.1111/febs.15300
|View full text |Cite
|
Sign up to set email alerts
|

Post‐transcriptional mechanisms regulating parathyroid hormone gene expression in secondary hyperparathyroidism

Abstract: Parathyroid hormone (PTH) regulates serum calcium levels and bone strength. Secondary hyperparathyroidism (SHP) is a common complication of chronic kidney disease (CKD) that correlates with morbidity and mortality. In experimental SHP, the increased PTH gene expression is due to increased PTH mRNA stability and is mediated by protein–PTH mRNA interactions. Adenosine–uridine‐rich binding factor 1 (AUF1) stabilizes and K‐homology splicing regulatory protein (KSRP) destabilizes PTH mRNA. The peptidyl‐prolyl cis/t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…The Pin -/- mice also had a 2-fold increase in PTH mRNA and protein content in the parathyroid glands, in agreement with their high serum PTH levels. These results support the central role for Pin1 in determining basal PTH levels in vivo (12, 29).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The Pin -/- mice also had a 2-fold increase in PTH mRNA and protein content in the parathyroid glands, in agreement with their high serum PTH levels. These results support the central role for Pin1 in determining basal PTH levels in vivo (12, 29).…”
Section: Introductionsupporting
confidence: 81%
“…Pin1-mediated KSRP Ser181 dephosphorylation favors KSRP-PTH mRNA 3'-UTR binding and thus PTH mRNA decay. In SHP, parathyroid Pin1 isomerase activity is decreased and phosphorylated Ser181 KSRP fails to induce PTH mRNA decay, resulting in increased PTH mRNA and serum levels (12,29,30).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in PTH gene expression in SHP is regulated by posttranscriptional mechanisms that alter PTH mRNA stability and levels. PTH mRNA stability is mediated by PTH mRNA–protein binding orchestrated by the cis-trans isomerase Pin1 [ 33 , 34 ]. microRNAs (miRNAs) also contribute to the stimulation of the parathyroid in SHP [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…We found that Pin1 mRNA was 30% higher (p < 0.01) in parathyroid adenomas vs. normal parathyroid tissues. Additional proteins that were related to RNA stability as well as protein synthesis and processing, DNA repair and cell growth were also dysregulated [26]. In another human study of single nucleotide polymorphisms (SNP) in the Pin1 gene promoter, in the Chinese Han population in Northwest China, Pin1 C667T genetic variants were associated with CKD SHP.…”
Section: Regulation Of Pth Mrna Stability By Protein-pth Mrna Interactions and Pin1mentioning
confidence: 99%
“…Therefore, increases in PTH gene expression are essential for a continued secretion of PTH. The increased PTH gene expression in experimental SHP induced by either uremia or prolonged hypocalcemia is due to post-transcriptional mechanisms that alter PTH mRNA stability and levels [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%